Asparagine-linked glycosylation of human chymotrypsin C (CTRC) is required for folding and secretion but not for enzyme activity - Bence, Melinda (2011)
Human chymotrypsin C (CTRC) plays a protective role in the pancreas by mitigating premature trypsinogen activation through degradation. Mutations that abolish activity or secretion of CTRC increase the risk for chronic pancreatitis. The aim of the present study was to determine whether human CTRC undergoes asparagine-linked (N-linked) glycosylation and to examine the role of this modification in CTRC folding and function. We abolished potential sites of N-linked glycosylation (Asn-Xaa-Ser/Thr) in human CTRC by mutating the Asn residues to Ser individually or in combination, expressed the CTRC mutants in HEK 293T cells and determined their glycosylation state using PNGase F and endo H digestion. We found that human CTRC contains a single N-linked glycan on Asn52. Elimination of N-glycosylation by mutation of Asn52 (N52S) reduced CTRC secretion about 10-fold from HEK 293T cells but had no effect on CTRC activity or inhibitor binding. Overexpression of the N52S CTRC mutant elicited endoplasmic reticulum stress in AR42J acinar cells, indicating that N-glycosylation is required for folding of human CTRC. Despite its important role, Asn52 is poorly conserved in other mammalian CTRC orthologs, including the rat which is monoglycosylated on Asn90. Introduction of the Asn90 site in a non-glycosylated human CTRC mutant restored full glycosylation but only partially rescued the secretion defect. We conclude that N-linked glycosylation of human CTRC is required for efficient folding and secretion, however, the N-linked glycan is unimportant for enzyme activity or inhibitor binding. The position of the N-linked glycan is critical for optimal folding, and it may vary among the otherwise highly homologous mammalian CTRC sequences.